Leadership in Islamic Boarding Schools - Aviva, Nailussa’adah; Ismail, Iriani (Indonesian Journal of Economic & Management Sciences, 2023)
Leadership in Islamic boarding schools is very important because the life or death and development of an Islamic boarding school will be seen in the pattern and leadership style of a kyai. Leadership authority in Islamic boarding schools rests with a kyai. Therefore, it is very natural and normal for the role of kyai to be highly respected in the growth of Islamic boarding schools. In order to be an inspiration and role model, it is necessary to form a dynamic learning community pattern. The problem formulations include: 1) what is meant by leadership in Islamic boarding schools. 2) what leadership styles exist in Islamic boarding schools. 3) What roles are applied to a kyai. This research uses a literature analysis method obtained from several literatures. From the research results, the success or failure of an Islamic boarding school depends on the leadership style applied by the kyai themselves. Leadership factors are still determining factors in effectiveness and efficiency. Apart from that, the vision and mission also have influences and interrelated elements. The elements used as a reference are those that are adapted to Islamic law, including: 1) ethics that are in accordance with the teachings of the Prophet Muhammad. 2) objective leaders, 3) leaders who have high credibility, 4) responsive leaders